POLITICAL AND CIVIL ACTIVITY OF SOCIAL WORKERS TO PURSUE SOCIAL JUSTICE - SKUČIENĖ, Daiva (Socialinė teorija, empirija, politika ir praktika, 2015)
The main objective of social work is social justice. The objective of social justice can be achieved through the micro and macro practices. So, the aim of this paper is to find what the political and civil activity of social workers as well as the understanding of social justice are. A few tasks were delivered for the implementation of this purpose. First, the review of the role of social work at macro practice and of advocators and their understanding of social justice was carried out; second, the political and civil activity of social workers was evaluated; third, the understanding of social justice by social workers was analysed, and finally, the conclusions were drawn.The main philosophical value for social work is social justice, which is the base for the advocacy of the client at macro level and which supports and enhances the individuals’ and society’s functioning. The previous researches show the content and functions of the political activity of social workers, emphasize the dynamic role of social work among civil society and social policy, reveal a liberal political ideology of social workers, analyse how this ideology has impacted the daily practice, disclose the means for the engagement in the political activity, define the skills for the purpose, and change the policy. Despite this, the macro level practice of social work is criticised in the contemporary socio-economic context: the voice of social work is weak; the social justice is undefended; seeking social welfare and dealing with social problems, the social work is focused only on behavioural change and it’s superficial, because it doesn’t involve the human life complexity, as such a function is only management; the social work recedes from social policy and social development. Thus, the profession neglects the “social” in social work, weakening the objective of social justice. The organisations of social work don’t put enough efforts in the disclosure of a demand of social services in communities.The aim of the paper was achieved applying secondary analyses of the European Social Survey 2010–2012 and the European value survey 2008. However, the small sample of Lithuanian social workers in these surveys doesn’t allow to summarise the findings for all social workers in the country. The findings revealed that the political activity of social workers is low. Social workers from all the European countries that participated in the surveys indicated that they are somewhat interested in politics, whereas Lithuanian social workers indicated that they are hardly interested. Social workers are not socially active either. Lithuanian social workers, who participated in the surveys, emphasized individual responsibility during the evalutation of various aspects of social justice more than the European social workers.
Keywords: Social work; social justice; political and civil activity